2022
DOI: 10.1519/jsc.0000000000004196
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Panoramic Ultrasound Measurement of the Cross-Sectional Area of the Vastus Medialis

Abstract: Minnehan, KS, Dexter, WW, Holt, CT, Scharnetzki, L, Alex, JP, Chin, KE, and Kokmeyer, DJ. Validation of panoramic ultrasound measurement of the cross-sectional area of the vastus medialis. J Strength Cond Res 37(1): 41–45, 2023—The cross-sectional area (CSA) of the vastus medialis (VM) is an independent predictor of important clinical outcomes in musculoskeletal conditions of the knee, such as pain and long-term function. Previous studies validated ultrasound (US) to measure larger muscles of the thigh, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The measurements of the muscular architecture acquired in this investigation are in good agreement with measurements of the quadriceps muscle assessed in earlier studies using ultrasonography [ 4 ]. The mean CSA of VM for the group A was (15.26+2.33), group B was (15.98+2.55), group C was (16.09+2.8) and group D was (13.94+2.7) which is coinciding with Minnehan et al [ 13 ]. There was significant inverse correlation between CSA of VM and age and positive correlation with BMI.…”
Section: Discussionsupporting
confidence: 86%
“…The measurements of the muscular architecture acquired in this investigation are in good agreement with measurements of the quadriceps muscle assessed in earlier studies using ultrasonography [ 4 ]. The mean CSA of VM for the group A was (15.26+2.33), group B was (15.98+2.55), group C was (16.09+2.8) and group D was (13.94+2.7) which is coinciding with Minnehan et al [ 13 ]. There was significant inverse correlation between CSA of VM and age and positive correlation with BMI.…”
Section: Discussionsupporting
confidence: 86%
“…To evaluate large muscle, the panoramic view of ultrasound can be used 22 25 . The panoramic view showed excellent inter-rater reliability and good correlation with MRI in measuring the cross-sectional areas of the quadriceps femoris (concordance correlation coefficient 0.78, p < 0.001) 22 , vastus medialis (interclass correlation coefficient about 0.98 and interrater reliability about 0.99) 23 , and hamstring muscles (correlation coefficient r ≥ 0.8) 24 . Thus, panoramic mode is a good tool for evaluating large muscles, such as the quadriceps femoris.…”
Section: Discussionmentioning
confidence: 86%
“…Sixth, this study did not aim to evaluate the variability in measurements. Although the previous studies reported that the panoramic view showed excellent inter-rater reliability and good correlation with MRI in measuring the cross-sectional areas of the quadriceps femoris 22 , vastus medialis 23 , and hamstring muscles 24 , further studies are needed to evaluate the variability in measurements in patients with sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…To measure acute muscle swelling researchers have used Ultrasound (US) images to measure changes in muscle size via muscle thickness measures [1,2] and Cross-Sectional Area (CSA) [3]. These measurements have both been shown to be valid when compared to CT [4] and MRI [5] scans, and reliable [6] amongst different clinicians. Muscle thickness has been shown to increase following resistance training [7], concentric [2], eccentric [8] and isometric [9] contractions, however it is not conclusive as others have shown size not to increase following resistance training [10].…”
Section: Introductionmentioning
confidence: 99%